Energetic segregation of B, C, N, O at the γ-TiAl/α2-Ti3Al interface via DFT approach. (April 2021) - Ouadah, O.; Merad, G.; Abdelkader, H. Si
Abstract: The effects of small atom impurities (B, C, N, O) segregation at the γ-TiAl/α2 -Ti3 Al interface were studied employing density functional theory (DFT) method. Energetic and bonding properties of the most stable interstitial configuration in the TiAl(111)/Ti3 Al(0001) interface with and without segregated solutes were investigated. Results found that the octahedral interstices are energetically the preferential location for interstitial impurities at the TiAl/Ti3 Al interface. Based on the data of interfacial energy, alloying with B and C atoms can destabilize the γ/α2 interface, while N and O atoms are beneficial for the stability by reducing the interface energy compared to the pure γ/α2 one. The most expected reductions are found for O impurity that makes the best stability. Besides, the calculation results of cleavage energy indicate that the segregation of B, N, and O will strengthen the γ/α2 interface, while the presence of C can maximally improve the ductility. Furthermore, charge density difference was computed to analyze interfacial atomic bonding behaviors. The mechanical properties are expected to be greatly improved in TiAl alloys reinforced wear-resistance coating and other functional devices after adding micro-alloying elements. Highlights: Micro-alloying atoms segregated between TiAl and Ti3 Al phases were analyzed. Preferential site occupations of alloying atoms are assessed. Interfacial and cleavage energies were investigated. Interfacial bond characteristics were revealed by charge density difference.